Komparasi Penyelesaian Problematika KDRT melalui Pengadilan Agama di Indonesia - Yusuf, Helmi (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2021)
Domestic Violence has become the subject of many divorce problems. This research on domestic violence aims to analyze domestic violence in the perspective of Islam and positive law and the background of its causes, this field research also reviews the Comparison of Settlement of Domestic Violence Problems through the Religious Courts of Tangerang City in 2016-2017. The results of this study reveal that the existence of Domestic Violence in the city of Tangerang is said to have not become the main posita, even though the existence of domestic violence has troubled the community, therefore it is appealed to the public to protect victims of violence and report the existence of such violence to the authorities or safe people. from perpetrators of violence in order to protect victims.